Review of Seneca Valley Virus: A Call for Increased Surveillance and Research - Zhang, Xiangle; Zhu, Zixiang; Yang, Fan; Cao, Weijun; Tian, Hong; Zhang, Keshan; Zheng, Haixue; Liu, Xiangtao (Frontiers in Microbiology, 2018)
Seneca Valley virus (SVV) has recently caused many vesicular diseases in pigs in different regions and countries. As a newly causative agent of porcine vesicular disease, SVV has evolved and spread quickly. It causes clinical signs similar to those of foot-and-mouth disease and results in significant economic losses. An increasing number of SVV outbreaks were reported in 2016 and 2017 in Brazil, United States, and China. However, few diagnostic methods have been established and no commercial vaccine has been available until now. Therefore, more attention needs to be paid to SVV, and urgent surveillance should be performed to prevent the spread of this virus. Although recent research has shed some light on SVV, there are still many aspects of the virus and the disease that are not yet fully understood, and many questions need to be resolved. This review presents current knowledge concerning SVV infection, epidemiology, pathogenicity, immune response, and diagnostic methods. This information will aid the design and adoption of effective prevention and control strategies to counter this viral pathogen.